An Analysis of Translation Method Used by Students of the Sixth Semester - Sarmila; Sujarwo; Suharti Siradjuddin (CV. Eureka Murakabi Abadi, 2023)
This study aims to determine the translation method used by students and the reasons they use it. This research is a qualitative research conducted on sixth semester students of English Education Study Program at Megarezky University Makassar. This study used five samples with purposive sampling technique. Researchers used instruments, observations, tests, interviews, and documentation. The data obtained were analyzed through data reduction, data presentation and conclusions. The results of this study indicate that there are several translation methods used in translating by students, of the eight translation methods students only use four translation methods, namely word by word translation, literal translation, free translation, and semantic translation. Where students use two to four methods in translating, and the reason they use these methods is because these methods are easy to apply in translating. Therefore, the researcher concludes that of the eight methods, only four translation methods are often used by students because they are easy to apply.